GEOMORPHOLOGICAL ANALYSIS FOR THE IDENTIFICATION OF SMALL VOLCANIC ISLANDS IN NORTH MALUKU, INDONESIA - Bachtiar W. Mutaqin; Warsini Handayani; Fredi Satya Candra Rosaji; Desy Wahyuningtyas; Muh Aris Marfai (JURNAL GEOGRAFI, 2021)
Indonesia, which is located in the Pacific Ring of Fire, has at least 100 active volcanoes that are spread among more than 17,000 islands. Several active volcanoes are located on small islands, so they require a greater effort in relation to disaster management, especially those related to volcano activities. However, research on the identification of small volcanic islands has not been widely carried out in Indonesia. This study tries to fill the gap using a geomorphological aspect approach, which consists of morphology, morphogenesis, morphochronology, and morphoaransement, to identify small volcanic islands in North Maluku Province. Literature review and spatial data collection were carried out to determine the parameters used in the identification of small volcanic islands. Based on the literature review, this study uses 5 (five) parameters, namely the island area, the type of material, the location / morphoaransement, the pattern of river flow, and the features of the landforms which include the presence of volcanic landform (morphochronology), slope, and morphology. Based on the spatial analysis using these 5 parameters, information is obtained that there are at least 6 of the 17 islands that meet the criteria to be called small volcanic islands in North Maluku. Data on small volcanic islands and their characteristics are important information to educate the public and improve preparedness.Keywords: morphology, morphogenesis, morphochronology, morphoaransement, small volcanic islands